2023
DOI: 10.1007/s11469-022-01004-8
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Impact of Emotional and Cognitive Factors on Anxiety Symptoms of Chinese Adolescents: a Serial Mediation Study

Abstract: The onset age of anxiety is decreasing worldwide, yet the majority of the study conducted on anxiety were focused on adult populations. This study aimed to investigate the mediating effect of psychological capital and coping style tendency on the relationship between emotional intelligence and anxiety in Chinese adolescents and provide empirical evidence for research and prevention. A cross-sectional study recruited 5747 participants from 5 randomly selected middle schools in the northeast China. Study results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…In order to alleviate the impact of emotional labor pressure, individuals will mobilize resources to cope. However, for those with poor resources, resource input will not make ends meet, resulting in resource loss, which may lead to deviant behavior [ 67 ]. As an important psychological resource, nurses with high psychological capital have positive psychological qualities such as self-efficacy, hope, resilience and optimism, which provide mental and psychological support for nurses, relieve work pressure [ 68 ], and reduce the harm of resource consumption.…”
Section: Discussionmentioning
confidence: 99%
“…In order to alleviate the impact of emotional labor pressure, individuals will mobilize resources to cope. However, for those with poor resources, resource input will not make ends meet, resulting in resource loss, which may lead to deviant behavior [ 67 ]. As an important psychological resource, nurses with high psychological capital have positive psychological qualities such as self-efficacy, hope, resilience and optimism, which provide mental and psychological support for nurses, relieve work pressure [ 68 ], and reduce the harm of resource consumption.…”
Section: Discussionmentioning
confidence: 99%
“…The integration of insights from various scholars sheds light on the intricate relationship between EI and PsyCap, elucidating their interconnectedness in shaping individual and organizational outcomes. From the predictors and ramifications of positive PsyCap among various occupational cohorts, such as Nigerian employees, graduate employees, and rural school teachers, as elucidated by Aderibigbe and Mjoli [74], Aderibigbe et al [65], Ali Yusuf and Widodo [75], Bhullar et al [76], Clarence et al [73], and D'Souza et al [71], to the nuanced dynamics of emotional and cognitive dimensions influencing anxiety symptoms and innovative behavior, as emphasized by Fei et al [77], Gao et al [78], Gallagher et al [79], and Gomes da Costa et al [47], the literature underscores the multifaceted nature of EI and PsyCap. Additionally, insights from studies by Hou et al [46], Jena and Pradhan [64], Liao et al [80], and Lim and Kim [68] illuminate the pivotal role of EI in shaping leadership dynamics, organizational citizenship behavior, and job performance.…”
Section: Insights From Studies On Ei and Psycapmentioning
confidence: 99%
“…The results showed that perceived learning support, learning selfmanagement, and peer influence significantly influenced affective learning participation and cognitive learning participation. As a result, these factors positively impacted sustained intentions to use mobile learning [35][36][37].…”
Section: Impacts On Students' Achievement Using Cognition and Affecti...mentioning
confidence: 99%